Small cell lung cancer recurring in the retina. Issue 4 (19th April 2022) - Marks, Sam; Woods, Brian; Higgins, Michaela; Connell, Paul
Abstract: Intraocular metastases are rare, usually isolating to the uveal tract. Retinal metastases are less common still, presenting a unique diagnostic and therapeutic challenge. This case observes a 66-year-old female ex-smoker presenting with unilateral painful vision loss 2 months from completion of definitive chemoradiotherapy for early-stage small cell lung cancer. A retinal lesion was discovered on examination and initially treated as viral retinitis without improvement. Two vitrectomy procedures were unable to confirm the diagnosis. Eventual retinal biopsy under general anaesthesia confirmed small cell lung cancer oligometastasis (7 months from completion of definitive chemoradiotherapy), without evidence of other sites of disease on imaging. She received local radiation to retina with resolution of eye pain. She eventually developed intrathoracic relapse of disease and was treated with palliative chemotherapy (14 months from completion of definitive chemoradiotherapy).